Communicative lexical exercises in teaching english in the field of "Public and Municipal Administration" - Abramova, Olga I. (2019)
The present article reveals specifics and essence of application of the main types of communicative lexical exercises for the development of students' speech productivity in the direction “State and Municipal Administration”. The authors analyze such types of exercises as responsive, situational, dispositive, compositional, initiative. This article highlights the features of the organization of speech interaction in practical classes and the use of English as a means of communication. The set of exercises presented in the article is aimed at developing students' speech productivity, practicing economic and managerial vocabulary and skills of unprepared speech in English. These types of lexical communicative exercises can be used in practical classes on the following subjects: "Foreign (English)", "Professional Foreign Language", "Business Foreign Language", "Home Reading", "Translation and Translation Studies". The relevance of the present article is due to the stable interest of modern methods of teaching a foreign language to the processes occurring in the language and the creation of new, more advanced methods of teaching students English in a higher educational institution. The main task of the teacher is to improve the use of types of communication exercises in practical classes in the English language, identifying conditions for improving the quality of learning and verbal productivity.